Enhanced photosuseeptibility in the insulatorto-metal phase transition in vanadium dioxide - Hilton, D; Prasankumar, R; Fourmaux, S; Cavalleri, A; Brassard, D; Khakani, E; Keiffer, J; Taylor, A; Averitt, R (Optical Society of America, 2007)
We use optical-pump terahertz-probe spectroscopy to measure the photoinduced phase transition in vanadium dioxide thin films. Our measurements reveal a fluence threshold needed to drive this transition that decreases with increasing temperature.